Lithium-manganese-nickel composite oxide, preparation method thereof, pole piece, battery and electric device

CN119301772AActive Publication Date: 2025-01-10CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202280094228.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-01-10
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

When spinel-type lithium-manganese-nickel composite oxide is used as a cathode material, it is prone to side reactions with the electrolyte, leading to the risk of cell bulging and capacity attenuation. In addition, the dissolution of Mn2+ ions leads to the destruction of the SEI film on the surface of the negative electrode, thereby accelerating battery capacity attenuation.

Method used

By regulating the crystal structure and elemental composition of the lithium manganese nickel composite oxide, especially controlling the peak intensity ratio between the (111) peak and the (400) peak in the X-ray diffraction spectrum within the range of 2.1≤I111/I400≤3.3, combined with doping Miscellaneous elements such as Si, P, Ru, Te, Ce, Ta, etc. improve the structural stability of the material, and through optimization of the heat treatment process, the structural stability of the lithium manganese nickel composite oxide is improved.

Benefits of technology

Significantly reduces the reactivity of lithium manganese nickel composite oxide and electrolyte, improves the overall performance and capacity of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301772A_ABST
    Figure CN119301772A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-manganese-nickel composite oxide and a preparation method thereof, a positive pole piece, a battery and an electric device. The crystal form of the lithium-manganese-nickel composite oxide is a spinel type, the ratio of the peak intensity I111 of a (111) peak to the peak intensity I400 of a (400) peak in an X-ray diffraction pattern of the lithium-manganese-nickel composite oxide is 2.1 < = I111 / I400 < = 3.3, the diffraction angle 2theta of the (111) peak is 18-19.5 degrees, and the diffraction angle 2theta of the (400) peak is 43.5-45 degrees. The lithium-manganese-nickel composite oxide has high stability and can improve the comprehensive performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Lithium manganese nickel composite oxide and preparation method thereof, pole piece, battery, and electrical device Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to lithium manganese nickel composite oxide and its preparation method, positive electrode sheet, battery, and electrical device. Background Art

[0002] Lithium-ion batteries have the advantages of high voltage, light weight, long cycle life, no memory effect, and good safety. They can be widely used in digital products such as mobile phones, digital cameras, and laptops, and power tools such as electric vehicles and hybrid electric vehicles. Lithium-ion batteries include positive electrode materials, negative electrode materials, isolation membranes, electrolytes, and current collectors. Among them, the positive electrode material is the key to restricting the overall performance and cost of lithium-ion batteries. Spinel-type lithium manganese nickel composite oxide can be used as a positive electrode material in batteries, but spinel-type lithium manganese nickel composite oxide has a high lithium intercalation and deintercalation potential, which causes serious side reactions between the positive electrode material and the electrolyte. The electrolyte is consumed and a large amount of gas is generated, which increases the risk of battery cell swelling and accelerates capacity attenuation. At the same time, the positive electrode material undergoes ion dissolution due to side reactions, in which Mn 2+ More dissolved, and the dissolved Mn 2+ It will deposit on the surface of the negative electrode, destroy the SEI film (Solid Electrolyte Interface), and accelerate the capacity decay of the negative electrode and the battery.

[0003] Summary of the Invention

[0004] The main technical problem solved by this application is to provide a spinel-type lithium manganese nickel composite oxide and its preparation method, positive electrode plate, battery and power device, which can improve the stability of the positive electrode active material and thus increase the capacity of the battery.

[0005] In order to solve the above technical problems, a technical solution adopted in the present application is to provide a spinel-type lithium manganese nickel composite oxide, wherein the crystal form of the lithium manganese nickel composite oxide is spinel-type, and the peak intensity I of the (111) peak in the X-ray diffraction spectrum of the lithium manganese nickel composite oxide is 111 The peak intensity of the (400) peak I 400 The ratio is 2.1≤I 111 / I 400 ≤3.3, wherein the (111) peak is a peak with a diffraction angle of 2θ = 18°-19.5°, and the (400) peak is a peak with a diffraction angle of 2θ = 43.5°-45°.

[0006] In some embodiments, the average chemical composition of the lithium manganese nickel composite oxide is Li 1+a M x Ni 0.5+z Mn1.5-x-z O 4-k , where 0 < a ≤ 0.3, 0 < x ≤ 0.2, -0.3 ≤ z ≤ 0.3, 0 ≤ k ≤ 0.2, and M includes one or more elements selected from Na, Si, P, S, Nb, Mo, Ru, Te, Ce, Ta, and W.

[0007] In some embodiments, the average chemical composition of the lithium manganese nickel composite oxide is Li 1+a M x N y Ni 0.5+z Mn 1.5-x-y-z O 4-k-q Q q , where 0 < a ≤ 0.3, 0 < x ≤ 0.2, 0 ≤ y ≤ 0.3, -0.3 ≤ z ≤ 0.3, 0 ≤ k ≤ 0.2, 0 ≤ q ≤ 0.5, M includes one or more elements selected from Na, Si, P, S, Nb, Mo, Ru, Te, Ce, Ta, and W, N includes one or more elements selected from Mg, Al, K, Sc, Ti, V, Cr, Fe, Co, Rb, Sr, Y, Zr, Rh, Sb, La, Sm, Gd, Yb, Lu, and Hf, and Q includes one or more elements selected from F, Cl, Br, and I.

[0008] In some embodiments, 1 ≤ a / x ≤ 20.

[0009] In some embodiments, 0.03 ≤ a ≤ 0.15.

[0010] In some embodiments, 0.002 ≤ x ≤ 0.1.

[0011] In some embodiments, in the X-ray diffraction pattern of the lithium manganese nickel composite oxide, there is at least one peak between diffraction angles 2θ = 21.5° - 24°, and the ratio of the intensity of the strongest peak between diffraction angles 2θ = 21.5° - 24° to the intensity of the (111) peak is 0 < I (21.5°-24°) / I 111 ≤ 3%.

[0012] In some embodiments, in a battery using the lithium manganese nickel composite oxide as the positive electrode material and Li as the negative electrode material, when charged at a charging rate of 0.1C, the ratio of the charging capacity in the 3.5 - 4.4V range to the total charging capacity in the 3.5 - 4.95V range is less than or equal to 15%.

[0013] In some embodiments, 0 < x + y + z ≤ 0.3.

[0014] In some embodiments, 2.4 ≤ I 111 / I 400≤2.8; 2≤a / x≤10; 0.05≤a≤0.12; 0.01≤x≤0.06; 0.005≤y≤0.05; 0.01≤z≤0.1; 0.01≤x+y+z≤0.1; 0.01≤q≤0.1; 0≤k≤0.1.

[0015] In some embodiments, the lithium manganese nickel composite oxide includes one or more of single crystal particles, quasi-single crystal particles, and secondary particles.

[0016] In some embodiments, the number of crystal grains contained in a single secondary particle is 1≤n≤8.

[0017] In some embodiments, the grain shape includes one or more of a spherical shape, an octahedron, a regular shape with sharp edges and cut corners on an octahedron, an octahedron with rounded corners, and / or a regular shape of a polyhedron with sharp edges and cut corners on an octahedron with rounded corners.

[0018] In some embodiments, the volume median particle size of the lithium manganese nickel composite oxide is 2 μm ≤ D V50 ≤20μm.

[0019] In some embodiments, the powder of the lithium manganese nickel composite oxide has a pH of 10≤pH≤12.

[0020] In some embodiments, the specific surface area of ​​the lithium manganese nickel composite oxide is 0 <BET≤0.8m 2 / g.

[0021] In order to solve the above technical problems, another technical solution adopted in this application is: providing a positive electrode plate, including a positive electrode material and a positive electrode current collector, and the positive electrode material includes any of the above lithium manganese nickel composite oxides.

[0022] In order to solve the above technical problems, another technical solution adopted in this application is: to provide a battery, including: a positive electrode plate, an isolation membrane and a negative electrode plate, the isolation membrane is located between the positive electrode plate and the negative electrode plate to play an isolation role, and the positive electrode plate includes any of the above positive electrode plates.

[0023] In some embodiments, the battery further comprises an electrolyte, and the electrolyte solvent of the electrolyte comprises one or more of fluorocarbonates, fluorocarboxylates, sulfones, and fluoroethers.

[0024] To solve the above technical problems, another technical solution adopted in this application is: to provide a method for preparing a lithium manganese nickel composite oxide, comprising: providing raw materials for the lithium manganese nickel composite oxide; and heat-treating the raw materials for the lithium manganese nickel composite oxide in an oxygen-containing atmosphere to obtain any of the above-mentioned lithium manganese nickel composite oxides.

[0025] In some embodiments, the heat treatment of the raw materials of the lithium manganese nickel composite oxide in an oxygen-containing atmosphere includes: heating the raw materials of the lithium manganese nickel composite oxide to T1, keeping the temperature for 2 - 50 h to obtain an intermediate of the lithium manganese nickel composite oxide; where 850°C ≤ T1 ≤ 1100°C.

[0026] In some embodiments, the preparation method of the lithium manganese nickel composite oxide further includes: heating the intermediate of the lithium manganese nickel composite oxide to T2, keeping the temperature for 0.5 - 20 h to obtain a preform of the lithium manganese nickel composite oxide; where T1 - 200°C ≤ T2 ≤ T1 and T2 ≥ 800°C.

[0027] In some embodiments, the preparation method of the lithium manganese nickel composite oxide further includes: heating the preform of the lithium manganese nickel composite oxide to T3, keeping the temperature for 5 - 30 h to obtain the lithium manganese nickel composite oxide; where 500°C ≤ T3 ≤ 800°C.

[0028] In some embodiments, providing the raw materials of the lithium manganese nickel composite oxide includes: according to the target components Li 1+a M x Ni 0.5+z Mn 1.5-x-z O 4-k providing stoichiometric Li2CO3, Ni 0.5+z Mn 1.5-x-z (OH) 4-2x 、M b O c powders, mixing them evenly to obtain the raw materials of the lithium manganese nickel composite oxide, where 0 < a ≤ 0.3, 0 < x ≤ 0.2, -0.3 ≤ z ≤ 0.3, 0 ≤ k ≤ 0.2, and M includes one or more elements of sodium (Na), silicon (Si), phosphorus (P), sulfur (S), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tellurium (Te), cerium (Ce), tantalum (Ta), tungsten (W).

[0029] The beneficial effect of this application is: different from the prior art, by adjusting the intensity ratio I 111 / I 400 of the characteristic peaks of the spinel-type lithium manganese nickel composite oxide within a preferred range, the structural stability of the lithium manganese nickel composite oxide can be improved, thereby reducing its reactivity with the electrolyte when used as a cathode material and enhancing the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] FIG. 1 is the X-ray diffraction pattern of some embodiments and comparative examples of this application;

[0031] FIG. 2 is the X-ray diffraction pattern of some embodiments and comparative examples of this application;

[0032] FIG3 is a first-cycle charging curve of button batteries according to some embodiments and comparative examples of the present application;

[0033] FIG4 is a morphology image of the positive electrode active material of Example 3 of the present application tested using a scanning electron microscope;

[0034] FIG5 is a morphology image of the positive electrode active material of Example 36 of the present application tested using a scanning electron microscope;

[0035] FIG6 is a morphology image of the positive electrode active material of Example 46 of the present application tested using a scanning electron microscope;

[0036] FIG7 is a morphology image of the positive electrode active material of Example 47 of the present application tested using a scanning electron microscope;

[0037] FIG8 is a morphology diagram of the positive electrode active material of Comparative Example 1 of the present application tested using a scanning electron microscope. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and effects of this application clearer and more specific, this application is further described in detail below with reference to the accompanying drawings and examples.

[0039] As used herein, the term "about" is used to describe and illustrate small variations. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely as well as an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values ​​are sometimes presented in this article in a range format. It should be understood that such range formats are for convenience and brevity and should be flexibly understood to include not only the numerical values ​​explicitly designated as range limits, but also all individual numerical values ​​or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.

[0040] In the detailed description and claims, a list of items linked by the term "at least one of" can mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A can contain a single element or multiple elements. Item B can contain a single element or multiple elements. Item C can contain a single element or multiple elements.

[0041] With the widespread use of electrochemical devices (e.g., lithium-ion batteries), people have increasingly higher requirements for their performance, especially the safety, stability, capacity, etc. of the batteries, and expect the batteries to have good comprehensive performance in all aspects. Lithium-ion batteries include a positive electrode, a negative electrode, a separator, an electrolyte, etc. The positive electrode includes a positive electrode current collector and a positive electrode material disposed on the positive electrode current collector. Among them, the positive electrode material is the key to restricting the overall performance of lithium-ion batteries. However, the currently used positive electrode materials are prone to serious side reactions with the electrolyte, which can lead to problems such as increased risk of cell swelling, accelerated negative electrode capacity decay and battery capacity decay. Generally, various measures can be used to improve the current problems, such as surface coating of the positive electrode material, structural control of the positive electrode material to reduce oxygen defects in the material, increasing the particle size of the positive electrode material, reducing the specific surface area of ​​the positive electrode material, surface modification of the positive electrode material to stabilize the material surface, and reducing contact between the electrolyte and the positive electrode material. However, these measures still have certain disadvantages.

[0042] In order to solve the above technical problems, the present application selects spinel lithium manganese nickel composite oxide as the positive electrode material, and regulates the crystal structure, elemental composition and content of the lithium manganese nickel composite oxide and the preparation process to improve the performance of the lithium manganese nickel composite oxide, improve the thermodynamic trend and growth dynamics of the lithium manganese nickel composite oxide to grow towards a more stable structure, thereby improving the structural stability of the lithium manganese nickel composite oxide, and further significantly improving the comprehensive performance of the lithium manganese nickel composite oxide used as a positive electrode material in the battery, specifically, it can increase the battery capacity. Among them, the lithium manganese nickel composite oxide refers to an oxide containing lithium manganese nickel, that is, in addition to lithium manganese nickel, other elements can also be included in the oxide, and therefore, it is also called a lithium manganese nickel composite oxide.

[0043] In some embodiments, the crystal form of the lithium manganese nickel composite oxide is a spinel type, and the peak intensity I of the (111) peak in the X-ray diffraction spectrum of the lithium manganese nickel composite oxide is 111 The peak intensity of the (400) peak I 400 The ratio is 2.1≤I 111 / I 400 ≤3.3, the (111) peak is a peak with a diffraction angle of 2θ = 18°-19.5°, and the (400) peak is a peak with a diffraction angle of 2θ = 43.5°-45°.

[0044] Among them, the lithium manganese nickel composite oxide can be tested using a powder X-ray diffractometer with CuKα1 radiation according to the standard JIS K 0131-1996. In the X-ray diffraction (XRD) spectrum, the (111) peak (peak position 2θ = 18°-19.5°) is the peak of the preferred growth basal plane of the lithium manganese nickel composite oxide crystal, and the (400) peak (peak position 2θ = 43.5°-45°) is the peak of the end face of the lithium manganese nickel composite oxide crystal growth. The end face here is the end face of theoretical growth. By regulating the characteristic peak intensity ratio of the lithium manganese nickel composite oxide within this range, the structural stability of the lithium manganese nickel composite oxide can be improved, thereby reducing its activity in reacting with the electrolyte when used as a positive electrode material, and improving the overall performance of the battery.

[0045] In one embodiment, the first preferential growth crystal plane of the spinel-type lithium-manganese-nickel composite oxide is the (111) plane, that is, the atoms spread and grow layer by layer along the (111) plane, so the stacking quality of the (111) plane determines the stability of the crystal structure. A spinel-type lithium-manganese-nickel composite oxide grain can have multiple (111) planes (such as the eight side faces in the outer shape of an octahedral grain) growing simultaneously, and the crystal faces contact each other to form (a00) side faces. Therefore, the (111) plane can be called the "basal plane" of the spinel structure, and the (a00) plane can be called the "end face" of the spinel structure. In the XRD spectrum, the ratio of the peak intensity of the basal plane (111) to the peak intensity of the end face (a00) is E=I 111 / I a00 , E can indicate the degree of preference of the crystal plane (111); the larger the E value, the greater the degree of preference of the (111) plane, the lower the energy of the (111) plane, and the smoother the stacking of the (111) plane, the more stable the overall structure of the spinel-type lithium-manganese-nickel composite oxide, and thus the stability of the battery using the material is improved. However, when the E value is too large, the crystal structure is too stable, which will lead to the lithium ion (Li + ) intercalation and deintercalation become difficult, which is not conducive to the dynamic performance and capacity of the battery. Therefore, E can also be called the crystal plane preference index to characterize the stability of the crystal structure. In the conventional XRD spectrum, the (111) peak and the (400) peak are two of the three strong peaks with relatively large intensity. In this application, the (111) peak and the (400) peak are selected as the characteristic peaks to consider the E value, that is, E = I 111 / I 400 .

[0046] In a preferred embodiment, 2.3≤I 111 / I 400 ≤3.0; further preferably, 2.4≤I 111 / I 400 ≤2.8. For example, I 111 / I 400It can be 2.2, 2.5, 2.6, 2.7, 2.9, etc. By controlling the crystal plane preference index E value within this range, the activity of the reaction between the lithium manganese nickel composite oxide and the electrolyte can be reduced while meeting the battery kinetic performance and capacity requirements, thereby improving the stability of the battery.

[0047] In some embodiments, the crystal growth direction and structural stability of the lithium manganese nickel composite oxide can be controlled by regulating the composition and content of the elements contained in the lithium manganese nickel composite oxide. That is, the E value can be controlled by regulating the composition and content of the elements contained in the lithium manganese nickel composite oxide.

[0048] In some embodiments, the average chemical composition of the lithium manganese nickel composite oxide is Li 1+a M x Ni 0.5+z Mn 1.5-x-z O 4-k , wherein 0<a≤0.3, 0<x≤0.2, -0.3≤z≤0.3, 0≤k≤0.2, and M includes one or more elements selected from sodium (Na), silicon (Si), phosphorus (P), sulfur (S), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tellurium (Te), cerium (Ce), tantalum (Ta), and tungsten (W).

[0049] Among them, in the lithium manganese nickel composite oxide provided by the present application, the Li content in the oxide is increased, that is, the ratio of the molar content of the Li position to the Ni / Mn position element is greater than 0.5. Increasing the Li content is conducive to the thermodynamic trend of the spinel-type lithium manganese nickel composite oxide to grow towards a stable structure. Specifically, the increase in Li content can promote the increase of the Mn valence state in the spinel structure, increase the Mn-O bond strength, and reduce the side reaction of the spinel-type lithium manganese nickel composite oxide with the electrolyte, that is, the increased Li can enter the Mn position in an appropriate amount to form Li doping, improve the structural stability of the material, and thus reduce the side reaction with the electrolyte. However, there is a contradiction between the thermodynamic trend of the spinel-type lithium manganese nickel composite oxide to grow towards a stable structure and the growth dynamics (that is, the kinetic trend of growth). Therefore, an increase in Li content will reduce the preference for the (111) face, that is, reduce the E value, and reduce the dynamics of the spinel-type lithium manganese nickel composite oxide to grow into a stable structure. In other words, increasing the Li content can improve the thermodynamic tendency of the spinel-type lithium-manganese-nickel composite oxide to grow toward a stable structure, while reducing the driving force for the spinel-type lithium-manganese-nickel composite oxide to grow toward a stable structure, that is, reducing the kinetic tendency.

[0050] Furthermore, the present application introduces the M element into the lithium manganese nickel composite oxide to modify the lithium manganese nickel composite oxide, so as to reconcile the contradiction between the thermodynamic tendency and growth kinetics of the spinel-type lithium manganese nickel composite oxide to grow toward a stable structure, thereby significantly improving the stability of the spinel-type lithium manganese nickel composite oxide structure. In other words, the doping of the M element can increase the kinetics of the spinel-type lithium manganese nickel composite oxide to grow toward a stable structure, thereby compensating for the weakening of the growth kinetics caused by the increase in Li content.

[0051] In some embodiments, M includes one or more elements selected from sodium (Na), silicon (Si), phosphorus (P), sulfur (S), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tellurium (Te), cerium (Ce), tantalum (Ta), and tungsten (W). Preferably, M includes one or more elements selected from Si, P, Ru, Te, Ce, and Ta; further preferably, M includes one or more elements selected from P, Ru, Te, and Ta. The M element may be distributed within the bulk of the spinel-type lithium-manganese-nickel composite oxide or on the surface of the material.

[0052] In this embodiment, the selected M element can stabilize the crystal structure of the spinel lithium-manganese-nickel composite oxide on the one hand, and on the other hand can capture hydrogen fluoride (HF) in the electrolyte, and the products of the side reactions are harmless to the battery system, significantly improving the overall performance of the battery.

[0053] In some embodiments, the doping amount x of the M element must match the Li content a to better balance the thermodynamic and kinetic trends of crystal growth, that is, to balance the Li content and the E value. To a certain extent, the more Li, the more M element is needed to achieve a balance.

[0054] In some embodiments, 1≤a / x≤20. In some preferred embodiments, 2≤a / x≤10. For example, a / x can be 4, 6, 8, 11, 12, 15, 17, 19, etc.

[0055] In some embodiments, 0.03≤a≤0.15; preferably, 0.05≤a≤0.12. For example, a can be 0.04, 0.06, 0.08, 0.09, 0.11, 0.13, 0.14, etc.

[0056] In some embodiments, 0.002≤x≤0.1; preferably, 0.01≤x≤0.06. For example, x can be 0.005, 0.008, 0.02, 0.04, 0.05, 0.08, 0.09, etc.

[0057] In this embodiment, by controlling the M element doping amount and the Li content within this range, the improvement effect can be optimized, and the battery capacity, kinetic performance and long-term performance of the battery using the material can be taken into account, such as extending the battery life.

[0058] In some embodiments, the average chemical composition of the lithium manganese nickel composite oxide is Li 1+a M x N y Ni 0.5+z Mn 1.5-x-y-z O 4-k-q Q q , wherein 0<a≤0.3, 0<x≤0.2, 0≤y≤0.3, -0.3≤z≤0.3, 0≤k≤0.2, 0≤q≤0.5, M includes one or more elements selected from Na, Si, P, S, Nb, Mo, Ru, Te, Ce, Ta, and W, N includes one or more elements selected from magnesium (Mg), aluminum (Al), potassium (K), scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), cobalt (Co), rubidium (Rb), strontium (Sr), yttrium (Y), zirconium (Zr), rhodium (Rh), antimony (Sb), lanthanum (La), samarium (Sm), gadolinium (Gd), ytterbium (Yb), lutetium (Lu), and hafnium (Hf), and Q includes one or more elements selected from fluorine (F), chlorine (Cl), bromine (Br), and iodine (I). The N and Q elements can be distributed in the bulk phase of the spinel-type lithium-manganese-nickel composite oxide or on the surface of the material.

[0059] Wherein, N element is an element that can enter Li position and / or Mn position and / or Ni position.In some preferred embodiments, N comprises one or more elements selected from K, Rb, Sr, Y, Rh, Sb, La, Sm, Gd, Yb, Lu, and Hf.

[0060] In this embodiment, N element is doped into the spinel-type lithium-manganese-nickel composite oxide as other cations. By introducing these elements, it is beneficial for E to reach the required range, improve the stability of the spinel-type lithium-manganese-nickel composite oxide structure, and slow down the side reactions between the material and the electrolyte. Among them, the improvement effect of the preferred elements is the most obvious.

[0061] In some preferred embodiments, 0 < y ≤ 0.3, more preferably, 0.001 ≤ y ≤ 0.1, and even more preferably, 0.005 ≤ y ≤ 0.05. For example, y can be 0.003, 0.008, 0.01, 0.07, 0.13, 0.19, 0.25, etc. By controlling the nitrogen doping amount within this range, the improvement effect is optimal, while also taking into account battery capacity, dynamic performance, and the long-term performance of batteries using this material.

[0062] In some preferred embodiments, 0.01≤z≤0.1. For example, z can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, etc. This means that the Ni content is also increased. Increased Ni helps to increase the average valence of Mn and stabilize the structure. Increased Ni can also form a rock salt phase on the grain surface, protecting the manganese-rich phase and reducing the probability of Mn dissolution.

[0063] In some preferred embodiments, 0 < x + y + z ≤ 0.3; more preferably, 0.005 ≤ x + y + z ≤ 0.2; and even more preferably, 0.01 ≤ x + y + z ≤ 0.1. For example, x + y + z can be 0.008, 0.03, 0.06, 0.09, 0.16, 0.21, 0.27, etc. In this embodiment, the total cation doping amount is limited; by controlling the total cation doping amount within this range, the material's capacity, kinetic performance, and the service life of the battery using the material can be balanced.

[0064] In some preferred embodiments, 0 < q ≤ 0.5, more preferably 0.001 ≤ q ≤ 0.2, and even more preferably 0.01 ≤ q ≤ 0.1. For example, q can be 0.006, 0.03, 0.07, 0.13, 0.18, 0.24, 0.33, 0.42, etc. The anion doping amount can be controlled, and the improvement effect is optimal when the anion is within this range.

[0065] In some preferred embodiments, 0 ≤ k ≤ 0.1. For example, k can be 0.003, 0.005, 0.007, 0.009, etc. By controlling the oxygen content, the oxygen deficiency of the material can be reduced. Reducing oxygen deficiency is beneficial for improving the structural stability of the material and slowing down the side reactions between the material and the electrolyte.

[0066] In some embodiments, the X-ray diffraction spectrum of the lithium manganese nickel composite oxide has at least one peak between the diffraction angle 2θ = 21.5°-24°, and the ratio of the intensity of the strongest peak between the diffraction angle 2θ = 21.5°-24° to the (111) peak is 0 < I (21.5°-24°) / I 111 ≤3%; preferably 0.2%≤I (21.5°-24°) / I 111 ≤2%, more preferably 0.5%≤I (21.5°-24°) / I 111 ≤1.5%. For example, (21.5°-24°) / I 111 It can be 0.3%, 0.8%, 1.2%, 1.7%, 2.6%, etc.

[0067] Among them, by regulating the type of modifying elements (M elements, N elements and Q elements), element distribution, element doping amount, etc., the peak position and peak intensity of the peak between 21.5°-24° can be regulated. The inventors of this application have found that the higher the peak intensity of the peak between 21.5°-24°, the more conducive it is to extending the service life of the battery using the material, but after the peak intensity exceeds a certain value, the battery capacity drops sharply and the life deteriorates. Therefore, in the present application scheme, when regulating the doping type and doping amount of each element in the lithium manganese nickel composite oxide, it is necessary to consider the E value and the ratio of the intensity of the peak between 21.5°-24° to the (111) peak at the same time to regulate the overall performance of the battery better. The composition and content of the obtained better material are described above.

[0068] In some embodiments, in a battery using lithium manganese nickel composite oxide as the positive electrode material and lithium as the negative electrode material, when charged at a 0.1C charge rate, the ratio R of the battery's charge capacity in the 3.5-4.4V range to the total charge capacity in the 3.5-4.95V range is less than or equal to 15%; preferably, R is less than or equal to 10%; more preferably, 4% ≤ R ≤ 10%. For example, R can be 1%, 3%, 5%, 6%, 7%, 8%, 9%, 12%, 14%, etc.

[0069] Among them, in a button cell with spinel lithium manganese nickel composite oxide as the positive electrode material and Li as the negative electrode material, the ratio of the charging capacity in the 3.5-4.4V range to the total charging capacity in the 3.5-4.95V range is called the 4V platform ratio. The larger the 4V platform ratio R, the higher the Mn 3+ The higher the content, the lower the average charge and discharge voltage. 3+ An increase in content will increase the risk of Mn dissolution, and a decrease in the average discharge voltage means a decrease in energy density. Therefore, the R value needs to be regulated not to be too large. However, the inventors of the present application have found that when the E value of the spinel-type lithium-manganese-nickel composite oxide increases, it is often accompanied by an increase in R. In order to balance the two values, the overall performance of the battery is regulated to be higher. The inventors of the present application have further found that regulating the doping type and doping amount of the M element can balance the E value and the R value. Reasonable regulation of the doping type and doping amount of the M element can increase the E value but not increase or even decrease the R value. Thus, a better material composition is obtained, and the specific component content is described above.

[0070] In some embodiments, the lithium manganese nickel composite oxide includes one or more of single crystal particles, quasi-single crystal particles, and secondary particles.

[0071] The particles within a single crystal are arranged regularly and periodically in three-dimensional space. In other words, the entire crystal is composed of a uniform spatial lattice in three dimensions, and the spatial arrangement of particles throughout the crystal is long-range ordered. Single crystal particles are also called primary particles. Primary particles can aggregate to form secondary particles. When a secondary particle contains only a few or a dozen grains, it is called a quasi-single crystal particle.

[0072] In some embodiments, the grain shape of the lithium manganese nickel composite oxide includes one or more of a spherical shape, an octahedron, a regular shape with sharp edges and corners of an octahedron, an octahedron with rounded corners, and / or a regular shape of a polyhedron with sharp edges and corners of an octahedron; preferably, the grain shape is an octahedron with rounded corners and / or a regular shape of a polyhedron with sharp edges and corners of an octahedron with rounded corners.

[0073] Among them, the surface of the octahedron and the polyhedron with regular shape is more conducive to the formation of Li + Conductive crystal faces enhance capacity and dynamic performance; spherical grains mitigate cracking and corrosion caused by stress concentration, improving the material's subsequent processing performance and the long-term lifespan of batteries using them. Rounded octahedrons and / or regular polyhedrons with rounded corners and sharpened edges combine the advantages of the first two types, balancing capacity, dynamic performance, and long-term stability.

[0074] In some embodiments, the lithium manganese nickel composite oxide further includes secondary particles, and the number of crystal grains contained in a single secondary particle is 1≤n≤8, preferably 1≤n≤3. For example, n can be 2, 4, 5, 6, 7, etc.

[0075] The surface of spinel lithium-manganese-nickel composite oxide particles is where side reactions are concentrated. The surface of the spinel lithium-manganese-nickel composite oxide grains is the most stable crystal plane for the Ni / Mn and Ni / Mn sites, while the M element dissolved in the spinel lithium-manganese-nickel composite oxide primarily resides in the Ni / Mn sites. Therefore, in single crystal particles, the M element is most stable when incorporated into the crystal lattice, allowing the M-containing surface coating to perfectly match the substrate surface, maximizing the M element's modification effect.

[0076] In addition, compared with polycrystals of the same particle size, the surfaces of single crystal particles are relatively stable crystal planes, with a smaller specific surface area. The probability of cracking and exposing unstable surfaces during processing and service is lower, which is beneficial to slowing down surface side reactions. Compared with polycrystals of the same grain size, single crystals are more conducive to dynamic performance due to their small particles and are also not easy to crack.

[0077] In some embodiments, the volume median particle size of the lithium manganese nickel composite oxide is 2 μm ≤ D V50 ≤20μm; preferably, 3μm≤DV50 ≤15μm, more preferably, 5μm≤D V50 ≤10μm. For example, D V50 It can be 4μm, 6μm, 8μm, 13μm, 18μm, etc. When the particle size is controlled within this optimized range, parameters such as single crystal, oxygen defects, and specific surface area can be better controlled.

[0078] In some embodiments, the powder pH of the lithium manganese nickel composite oxide is 10 ≤ pH ≤ 12. Compared to conventional spinel-type lithium manganese nickel composite oxides having a pH of 7-10, the spinel-type lithium manganese nickel composite oxide of the present application has a stronger alkalinity, which can neutralize the strong acid generated under high voltage and reduce surface damage to the positive electrode material. Excessive alkalinity is detrimental to processing performance and is prone to moisture absorption and reaction with the binder, thereby deteriorating battery performance.

[0079] In some embodiments, the specific surface area of ​​the lithium manganese nickel composite oxide is 0<BET≤0.8m 2 / g; preferably, 0<BET≤0.5m 2 / g, more preferably, 0.1≤BET≤0.4m 2 / g. For example, it can be 0.2m 2 / g, 0.3m 2 / g, 0.6m 2 / g, 0.7m 2 / g, etc. Specific surface area can be measured using gas adsorption. A smaller specific surface area can slow down surface side reactions. However, the specific surface area is significantly affected by the coating state. For example, coating nanoparticles significantly increases the specific surface area, but the active specific surface area actually decreases.

[0080] In some embodiments, the crystal growth direction and structural stability of the lithium manganese nickel composite oxide can be controlled by regulating the preparation process parameters of the lithium manganese nickel composite oxide. That is, the E value can be controlled by regulating the preparation process parameters of the lithium manganese nickel composite oxide.

[0081] In some embodiments, a solid phase synthesis method can be used to prepare lithium manganese nickel composite oxide. The specific preparation method includes: providing raw materials for lithium manganese nickel composite oxide, and heat treating the raw materials for lithium manganese nickel composite oxide in an oxygen-containing atmosphere to obtain the lithium manganese nickel composite oxide of any of the above embodiments.

[0082] The raw materials of lithium manganese nickel composite oxide can be prepared according to the component content of the target lithium manganese nickel composite oxide, and the raw materials used are specifically adjusted according to the type of doping element. If the doped cation is a metal cation, the raw materials used can be the metal oxide (M) corresponding to the cation. b O c); When the doped cation is an inorganic cation, it can be the corresponding ammonium salt, carbonate, etc., and Li2CO3, Ni 0.5+z Mn 1.5-x-z (OH) 4-2x 、M b O c etc. as raw materials for lithium manganese nickel elements.

[0083] After mixing the raw material powders, heat treatment is performed in an oxygen-containing atmosphere to obtain the corresponding lithium manganese nickel composite oxide. The structure of the obtained lithium manganese nickel composite oxide can be stabilized by controlling the heating temperature, time, reaction atmosphere, etc.

[0084] In some embodiments, the method for preparing lithium manganese nickel composite oxide includes:

[0085] S110: raising the temperature of the raw material of the lithium manganese nickel composite oxide to T1, and sintering at the temperature T1 to obtain a lithium manganese nickel composite oxide intermediate.

[0086] S120: raising the temperature of the lithium manganese nickel composite oxide intermediate to T2, and sintering at the temperature T2 to obtain a lithium manganese nickel composite oxide preform.

[0087] S130: raising the temperature of the lithium manganese nickel composite oxide preform to T3 and performing annealing treatment to obtain the lithium manganese nickel composite oxide.

[0088] In some embodiments, 850°C ≤ T1 ≤ 1100°C, preferably 900°C ≤ T1 ≤ 1000°C. For example, T1 can be 880°C, 930°C, 950°C, 980°C, 1000°C, 1060°C, etc. The sintering time is 2-50 hours. Specifically, the raw material of the lithium manganese nickel composite oxide is heated to T1 and kept at T1 for 2-50 hours, for example, 8 hours, 15 hours, 23 hours, 31 hours, 42 hours, etc.

[0089] In some embodiments, T1-200°C ≤ T2 ≤ T1 and T2 ≥ 800°C; preferably, 850 + (T1-900) / 4°C ≤ T2 ≤ T1-(T1-900) / 4°C. For example, T2 can be 820°C, 850°C, 880°C, 910°C, 960°C, 1000°C, etc. The sintering time is 0.5-20 hours. Specifically, the lithium manganese nickel composite oxide intermediate can be heated to T2 and maintained at T2 for 0.5-20 hours, for example, 2 hours, 5 hours, 8 hours, 12 hours, 15 hours, 18 hours, etc.

[0090] In some embodiments, 500°C ≤ T3 ≤ 800°C, preferably 600°C ≤ T3 ≤ 700°C. For example, T3 may be 520°C, 560°C, 630°C, 680°C, 710°C, 750°C, etc. The annealing time may be 5-30 hours. Specifically, the lithium manganese nickel composite oxide preform may be heated to T3 and then maintained at T3 for 5-30 hours, for example, 8 hours, 14 hours, 18 hours, 23 hours, 27 hours, etc.

[0091] Among them, the appropriate temperature T1 and its holding time are important parameters to ensure the grain size, oxygen defect content, element distribution, etc. The appropriate temperature T2 and holding time have an important influence on the roundness of the grains, the oxygen defect content and the R value. Annealing is beneficial to reduce the R value, reduce oxygen defects and improve the stability of the material. In this embodiment, by reasonably regulating the temperature range of T1, T2 and T3, and the reaction time of steps S110, S120 and S130, the volume median particle size of the obtained material can be controlled to 2μm≤D V50 ≤20μm, lower oxygen vacancy defects, higher E value, lower R value, and specific material performance parameters are described in the above embodiment and will not be repeated here.

[0092] In some embodiments, the above steps S120 and S130 are optional, and only one or both may be performed; S120 needs to be performed after cooling to a lower temperature after S110; S130 can be performed after the previous heat treatment process is cooled, or it can be directly combined.

[0093] In some embodiments, the oxygen-containing atmosphere can be air, oxygen, an air-oxygen mixture, or the like.

[0094] The present application also provides a positive electrode plate, which includes a positive electrode material and a positive electrode current collector, and the positive electrode material is the lithium manganese nickel composite oxide described in any of the above embodiments.

[0095] In some embodiments, the positive electrode material also includes a positive electrode conductive material, thereby giving the electrode conductivity. The positive electrode conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of positive electrode conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof. In some embodiments, the positive current collector may be aluminum (Al).

[0096] The present application also provides an electrochemical device, which includes any device that generates an electrochemical reaction, and specific examples thereof include all types of primary batteries or secondary batteries. Lithium secondary batteries may include lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, or lithium ion polymer secondary batteries.

[0097] In some embodiments, the battery includes a positive electrode sheet, a separator and a negative electrode sheet. The separator is located between the positive electrode sheet and the negative electrode sheet to serve as an isolation. The positive electrode sheet includes the positive electrode sheet described in any of the above embodiments.

[0098] In some embodiments, the negative electrode includes a current collector and a negative electrode active material layer disposed on the current collector. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. For example, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , one or more of Li-Al alloys.

[0099] In some embodiments, the electrolyte solvent includes one or more of fluorocarbonates, fluorocarboxylates, sulfones, and fluoroethers. One or more of fluorocarbonates, fluorocarboxylates, and sulfones can be selected. The selected electrolyte is a high-voltage resistant electrolyte, which has reduced acidity at high voltages, significantly reducing surface side reactions and improving battery stability.

[0100] In some embodiments, the use of the electrochemical device of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. That is, an electrical device is provided. In some embodiments, the electrochemical device of the present application can be used in, but is not limited to, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors.

[0101] The preparation of lithium-ion batteries is described below using lithium-ion batteries as an example and in combination with specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.

[0102] 1. Preparation of the positive electrode

[0103] Preparation of positive electrode active materials

[0104] Raw material powders corresponding to the stoichiometric ratio of the target positive electrode active material composition were weighed and uniformly mixed to obtain a raw material mixture powder. The raw material mixture powder was heated to T1 in an air atmosphere, held at this temperature for t1, and then cooled to room temperature to obtain a semi-finished product. The semi-finished product was heated to T2 in an air atmosphere, held at this temperature for t2, and then cooled to room temperature to obtain a preform. The preform was heated to T3 in an air atmosphere, held at this temperature for t3, and then cooled to room temperature to obtain a lithium nickel manganese composite oxide. The specific target composition, raw materials used, and preparation process parameters are detailed in Tables 1 and 2.

[0105] 2. Battery (button cell) assembly

[0106] The positive electrode material is assembled into a button cell using a lithium sheet as the counter electrode. Specifically, lithium nickel manganese composite oxide is mixed with conductive carbon black (Super P) and PVDF in a weight ratio of 90:5:5, and an appropriate amount of solvent N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil and dried after coating to obtain a positive electrode sheet. The loading amount of lithium nickel manganese composite oxide on the positive electrode sheet is 0.016g / cm 2 Provide electrolyte. Using a 12μm-thick polypropylene film (Φ16mm) as a separator, place the lithium sheet, separator, and positive electrode sheet in order, placing the separator between the metal lithium sheet and the positive electrode to provide isolation. Inject the electrolyte and assemble into a CR2030 button cell. Let stand for 4 hours to obtain the button cell.

[0107] Among them, the electrolyte used in Comparative Example 1-8 and Example 1-61 is a mixed solution of carbonate and fluorocarbonate containing 1 mol / L LiPF6, with carbonate:fluorocarbonate = 1:1.

[0108] The electrolytes used in Comparative Examples 9 and 10 contained only carbonate.

[0109] 3. Production of soft pack batteries

[0110] The positive electrode active material is assembled into a soft pack battery. Specifically, lithium nickel manganese composite oxide is mixed with conductive carbon black (Super P) and PVDF in a weight ratio of 96:2.5:1.5, and an appropriate amount of solvent N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil and dried after coating to obtain a positive electrode sheet. The loading of lithium nickel manganese composite oxide on the positive electrode sheet is 0.016g / cm 2The negative electrode active material artificial graphite, conductive agent carbon black (Super P), binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose were fully stirred and mixed in an appropriate amount of solvent deionized water at a mass ratio of 96:1:1:2 to form a uniform negative electrode slurry; the negative electrode slurry was evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, the negative electrode sheet was obtained. The loading amount of negative electrode active material on one side of the negative electrode current collector is 0.007g / cm 2 A mixed solution of carbonate, fluorocarbonate, or other similar materials containing 1 mol / L LiPF6 is provided as the electrolyte. A 12 μm thick polypropylene film is used as the separator. The positive electrode, separator, and negative electrode prepared above are placed in order, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then processed and formed, and packaged in an aluminum-plastic bag. The electrolyte is then injected, and the cells are packaged and then charged to capacity to produce a soft-pack cell.

[0111] Among them, the electrolyte used in Comparative Example 1-8 and Example 1-61 is a mixed solution of carbonate and fluorocarbonate containing 1 mol / L LiPF6, with carbonate:fluorocarbonate = 1:1.

[0112] The electrolytes used in Comparative Examples 9 and 10 contained only carbonate.

[0113] 4. The relevant parameter testing process of the positive electrode active materials of the examples and comparative examples of the present application is as follows:

[0114] (1) XRD test

[0115] The X-ray diffraction pattern of the spinel-type nickel-manganese-lithium composite oxide material was measured using CuKα1 radiation in accordance with JIS K 0131-1996, General Rules for X-ray Diffraction Analysis Methods.

[0116] (2) Element content test

[0117] The content of each element in the spinel nickel-manganese-lithium composite oxide material was measured by inductively coupled plasma atomic emission spectrometry according to EPA 6010D-2014.

[0118] (3) Morphology test

[0119] The positive electrode active materials of all the examples and comparative examples were tested using a ZEISS sigma 300 scanning electron microscope and then tested according to the standard JY / T010-1996 to observe the morphology of the samples.

[0120] (4) Particle size test

[0121] Referring to the laser particle size analyzer diffraction method of GB / T19077-2016, take a clean beaker, add an appropriate amount of the sample to be tested, add a surfactant and then a dispersant. After sufficient dispersion, use a laser particle size analyzer to measure the particle size distribution characteristics (shading degree: 8%-12%).

[0122] (5) Specific surface area test

[0123] According to GB / T 19587-2004 gas adsorption BET method, after the sample is heated and degassed, the adsorption amount of gas on the solid surface at different adsorption pressures is measured at a constant low temperature. The monolayer adsorption amount of the sample is obtained based on the BET multilayer adsorption theory and its formula, and the specific surface area per unit mass of the solid sample is calculated.

[0124] 5. Power-off test and 4V charging platform R value calculation

[0125] At 25° C., button cells prepared from the positive electrode active materials of each embodiment / comparative example were charged at a constant current of 0.1 C to a voltage of 4.95 V, and the charging capacity (C1) of 3.5-4.4 V and the charging capacity (C2) of 3.5-4.95 V were intercepted from the original charging data.

[0126] The proportion of charging capacity on the 4V platform is R=C1 / C2.

[0127] 6. Soft pack electrical performance test

[0128] (1) Initial discharge energy density test of positive electrode active materials in soft pack batteries

[0129] The prepared soft-pack battery was used as the test object.

[0130] At 25°C, the soft-pack battery is charged at a constant current of 0.3C to a voltage of 4.8V, then charged at a constant voltage of 4.8V to a current of 0.05C. After standing for 5 minutes, the soft-pack battery is discharged at a constant current of 0.33C to a voltage of 3.5V. The discharge energy is the battery discharge energy. Dividing this energy by the mass of the positive active material in the battery is the initial discharge energy density of the positive active material.

[0131] (2) High temperature cycle performance test of soft pack batteries

[0132] The prepared soft-pack battery was used as the test object.

[0133] At 45°C, the soft-pack battery is charged at a constant current of 0.5C to a voltage of 4.8V. Then, it is charged at a constant voltage of 4.8V to a current of 0.05C. After standing for 5 minutes, the soft-pack battery is discharged at a constant current of 0.5C to a voltage of 3.5V. This is a charge cycle process. The discharge capacity of this time is the discharge capacity of the first cycle. After the cyclic charge test is carried out according to the above method, the cycle is completed until the discharge capacity decays to 80% of the initial value. The total number of cycles is the high-temperature cycle life.

[0134] (3) Soft-pack battery high-temperature full-charge storage performance test

[0135] The prepared soft-pack battery was used as the test object.

[0136] At 25°C, charge the soft-pack battery at a constant current of 0.3C to a voltage of 4.8V, then charge at a constant voltage of 4.8V to a current of 0.05C. The battery is then placed at 45°C and fully discharged every 10 days. A full charge and discharge cycle is then performed at 25°C, and the discharge capacity value Cn is extracted. Fully charge the battery again and continue to store it at 45°C. Storage is terminated when the discharge capacity Cn decays to 80% of its initial value. The total storage time at 45°C after full charge is the high-temperature full-charge storage time.

[0137] Table 1: Preparation process parameters of various examples and comparative examples

[0138] Sample No. Raw material composition T1 / ℃t1 / hT2 / ℃t2 / hT3 / ℃t3 / h Comparative Example 1Li2CO3, Ni 0.5 Mn 1.5 (OH)495020 / / / / 65020Comparative Example 2Li2CO3、Ni 0.5 Mn 1.5 (OH)495020 / / / / / / / / Example 1Li2CO3, Ni 0.5 Mn 1.5 (OH)495020 / / / / / / / / Example 2Li2CO3, Ni 0.5 Mn 1.5 (OH)495020 / / / / 65020 Example 3 Li2CO3, Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / / / / / Example 4Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、TeO295020 / / / / / / / / Example 5Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92、SiO295020 / / / / / / / / Example 6Li2CO3、Ni 0.5 Mn 1.49 (OH) 3.98 、RuO295020 / / / / / / / / Example 7Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、CeO295020 / / / / / / / / Example 8Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、CeO295020 / / / / / / / / Example 9Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、Nb2O595020 / / / / / / / / Example 10Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、Ta2O595020 / / / / / / / / Example 11Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、WO395020 / / / / / / / / Example 12Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、TeO2、CeO295020 / / / / / / / / Example 13Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、Te2O5、Ta2O595020 / / / / / / / / Example 14Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、Li2SO4、WO395020 / / / / / / / / Comparative Example 3Li2CO3、Ni 0.49 Mn 1.5 (OH) 3.98 、Cr2O395020 / / / / / / / / Example 14Li2CO3、Ni 0.48 Mn 1.47 (OH) 3.9 、NH4H2PO4、Cr2O395020 / / / / / / / / Example 15Li2CO3、Ni 0.48 Mn 1.46 (OH) 3.88、NH4H2PO4、TeO2、Al2O395020 / / / / / / / / Example 16Li2CO3、Ni 0.48 Mn 1.47 (OH) 3.9 、NH4H2PO4、TeO2、Sb2O595020 / / / / / / / / Comparative Example 4Li2CO3、Ni 0.5 Mn 1.5 (OH)4、LiF95020 / / / / / / / / Example 17Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、LiF95020 / / / / / / / / Example 18Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、LiI95020 / / / / / / / / Example 19Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、TeO2、LiF95020 / / / / / / / / Example 20Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、CeO2、LiF95020 / / / / / / / / Comparative Example 5Li2CO3、Ni 0.5 Mn 1.48 (OH) 3.96 、Al2O3、LiF95020 / / / / / / / / Example 21Li2CO3、Ni 0.48 Mn 1.47 (OH) 3.9 、NH4H2PO4、Al2O3、LiF95020 / / / / / / / / Example 22Li2CO3、Ni 0.48 Mn 1.46 (OH) 3.88 、NH4H2PO495020 / / / / / / / / Example 23Li2CO3、Ni 0.49 Mn 1.46 (OH) 3.9 、NH4H2PO495020 / / / / / / / / Example 24Li2CO3、Ni 0.49 Mn 1.48 (OH) 3.94 、NH4H2PO495020 / / / / / / / / Example 25Li2CO3、Ni 0.5 Mn 1.49 (OH)3.98 、NH4H2PO495020 / / / / / / / /

[0139] Example 26 Li2CO3, Ni 0.5 Mn 1.495 (OH) 3.99 、NH4H2PO495020 / / / / / / / / Example 27Li2CO3、Ni 0.5 Mn 1.497 (OH) 3.994 、NH4H2PO495020 / / / / / / / / Example 28Li2CO3、Ni 0.5 Mn 1.49 (OH) 3.98 、NH4H2PO495020 / / / / / / / / Example 29Li2CO3、Ni 0.49 Mn 1.48 (OH) 3.94 、NH4H2PO495020 / / / / / / / / Example 30Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / / / / / Example 31Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / / / / / Example 32Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / / / / / Comparative Example 6Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / / / / / Example 33Li2CO3、Ni 0.5 Mn 1.498 (OH) 3.996 、NH4H2PO495020 / / / / / / / / Example 34Li2CO3、Ni 0.5 Mn 1.49 (OH) 3.98 、NH4H2PO495020 / / / / / / / / Example 35Li2CO3、Ni 0.48 Mn 1.46 (OH) 3.88 、NH4H2PO495020 / / / / / / / / Example 36Li2CO3、Ni 0.47 Mn 1.43 (OH)3.8 、NH4H2PO495020 / / / / / / / / Example 37Li2CO3、Ni 0.45 Mn 1.35 (OH) 3.6 、NH4H2PO495020 / / / / / / / / Comparative Example 7Li2CO3、Ni 0.44 Mn 1.32 (OH) 3.52 、NH4H2PO495020 / / / / / / / / Comparative Example 8Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO480020 / / / / / / / / Example 38Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO485020 / / / / / / / / Example 39Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO490020 / / / / / / / / Example 40Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4100020 / / / / / / / / Example 41Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4110020 / / / / / / / / Example 42Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4120020 / / / / / / / / Example 43Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO49502 / / / / / / / / Example 44Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495050 / / / / / / / / Example 45Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4950208005 / / / / Example 46Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92、NH4H2PO4950208652 / / / / Example 47Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4950209351 / / / / Example 48Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4950209500.5 / / / / Example 49Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4950208650.5 / / / / Example 50Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4950208658 / / / / Example 51Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO49502086520 / / / / Example 52Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / 50030Example 53Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / 60025Example 54Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / 70015Example 55Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / 78010Example 56Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / 6505Example 57Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / 65030Example 58Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92、NH4H2PO495020865265010Example 59Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO4、CeO2、LiF95020900170010Example 60Li2CO3、Ni 0.48 Mn 1.47 (OH) 3.9 、NH4H2PO4、Cr2O3、LiI95020900167015Example 61Li2CO3、Ni 0.48 Mn 1.47 (OH) 3.9 、NaOH、SiO2、TiO2、LiF95020900164020Comparative Example 9Li2CO3、Ni 0.5 Mn 1.5 (OH)495020 / / / / 65020Comparative Example 10Li2CO3、Ni 0.49 Mn 1.47 (OH) 3.92 、NH4H2PO495020 / / / / / / / /

[0140] Table 2: Composition and performance parameters of the positive electrode materials of various embodiments and comparative examples

[0141]

[0142]

[0143] Table 3: Battery performance parameters of various examples and comparative examples

[0144]

[0145]

[0146] The results show that when the average Li content ratio of the spinel-type lithium-containing manganese-nickel composite oxide is greater than 1, there is M element modification, and the E value (I 111 / I 400 ) is greater than or equal to 2.3 and less than or equal to 3.0, the battery prepared using the material as the positive electrode active material has good comprehensive performance, specifically good cyclability, high storage performance, energy density and comprehensive coefficient of electrical performance.

[0147] Please refer to Figures 1 and 2, which are X-ray diffraction patterns of some embodiments and comparative examples of this application. Specifically including the X-ray diffraction patterns of Comparative Example 1, Example 2, Example 3, Example 29, Example 42, and Comparative Example 7. Referring to the data in Tables 2 and 3, the E value of Comparative Example 1 is too small, which makes the stability of the positive electrode material poor, and thus leads to poor cyclability and storage performance of the battery, and the comprehensive coefficient of electrical performance also becomes low. It can be seen from Examples 1-2 and Comparative Example 1 that when the E value is in the expected range (2.3-3.0), the energy density and storage performance of the battery are improved, but the storage performance and comprehensive performance are not significantly improved; this shows that controlling the E value range can improve battery performance, but due to the low lithium content in Examples 1-2, the comprehensive performance of the battery is slightly low, which shows that it is necessary to comprehensively balance multiple parameters to improve the comprehensive performance of the battery. In other words, controlling the E value range can solve the technical problems proposed in this application of improving the stability of the positive electrode material and increasing the battery capacity. In other words, the present application does not limit the Li content ratio to greater than 1. When the Li content ratio is not greater than 1, the E value can also be achieved within the predetermined range. Combining Examples 3-4, it can be seen that when the E value is regulated within the expected range and the Li content ratio is greater than 1, the various performances of the battery are significantly improved, providing comprehensive performance.

[0148] It can be seen from Examples 5-21 and Comparative Examples 3-5 that regulating the doping of M, N, and Q elements in lithium manganese nickel composite oxides can also regulate and improve battery performance. The doping of M element can coordinate with regulating the E value within a predetermined range.

[0149] It can be seen from Examples 22-37 and Comparative Examples 6-7 that by rationally adjusting the Li content and the M element content, the comprehensive performance of the battery can be improved, with good cyclability, high storage performance, higher energy density and comprehensive electrical performance coefficient.

[0150] Examples 38-58 and Comparative Example 2 demonstrate that battery performance can be improved by manipulating the preparation process of the lithium manganese nickel composite oxide, with the E value being controlled within a predetermined range. Example 42 demonstrates that even high-temperature treatment can achieve an E value within the predetermined range, albeit at excessively high temperatures and with high energy consumption. In other words, even with a non-preferred process, oxide performance can be controlled by simply manipulating the component content.

[0151] Please refer to Figure 3, which shows the first-cycle charging curves of button-type batteries according to some examples and comparative examples of this application. Specifically, these curves include those for Comparative Examples 1 and 2, Example 1, and Example 4. Referring to the data in Tables 2 and 3 together, it can be seen that the 4V platform ratio R value of the positive electrode active material provided in this application is within a reasonable range, resulting in excellent overall battery performance.

[0152] Please refer to Figures 4 to 8. Figure 4 is a morphology image of the positive electrode active material of Example 3 of the present application tested using a scanning electron microscope; Figure 5 is a morphology image of the positive electrode active material of Example 36 of the present application tested using a scanning electron microscope; Figure 6 is a morphology image of the positive electrode active material of Example 46 of the present application tested using a scanning electron microscope; Figure 7 is a morphology image of the positive electrode active material of Example 47 of the present application tested using a scanning electron microscope; and Figure 8 is a morphology image of the positive electrode active material of Comparative Example 1 of the present application tested using a scanning electron microscope. The positive electrode active material provided in the present application includes single crystal particles. Compared with polycrystalline particles of the same particle size, the surface of single crystal particles are more stable crystal planes, have a smaller specific surface area, and are less likely to crack and expose unstable surfaces during processing and service, which is beneficial for slowing down surface side reactions. Compared with polycrystalline particles of the same grain size, single crystal particles are more conducive to dynamic performance due to their smaller particles and are also less prone to cracking.

[0153] The above description is only an implementation method of the present application and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the description and drawings of this application, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A lithium manganese nickel composite oxide, wherein, The crystal form of the lithium manganese nickel composite oxide is spinel type, and in the X-ray diffraction pattern of the lithium manganese nickel composite oxide, the peak intensity I of the (111) peak 111 and the peak intensity I of the (400) peak 400 have a ratio of 2.1 ≤ I 111 / I 400 ≤ 3.3, where the (111) peak is the peak with a diffraction angle 2θ = 18° - 19.5°, and the (400) peak is the peak with a diffraction angle 2θ = 43.5° - 45°.

2. The lithium manganese nickel composite oxide according to claim 1, wherein, The average chemical composition of the lithium manganese nickel composite oxide is Li 1+a M x Ni 0.5+z Mn 1.5-x-z O 4-k , where 0 < a ≤ 0.3, 0 < x ≤ 0.2, -0.3 ≤ z ≤ 0.3, 0 ≤ k ≤ 0.2, and M includes one or more elements selected from Na, Si, P, S, Nb, Mo, Ru, Te, Ce, Ta, and W.

3. The lithium manganese nickel composite oxide according to claim 1 or 2, wherein, The average chemical composition of the lithium manganese nickel composite oxide is Li 1+a M x N y Ni 0.5+z Mn 1.5-x-y-z O 4-k-q Q q , where 0 < a ≤ 0.3, 0 < x ≤ 0.2, 0 ≤ y ≤ 0.3, -0.3 ≤ z ≤ 0.3, 0 ≤ k ≤ 0.2, 0 ≤ q ≤ 0.5, M includes one or more elements selected from Na, Si, P, S, Nb, Mo, Ru, Te, Ce, Ta, W; N includes one or more elements selected from Mg, Al, K, Sc, Ti, V, Cr, Fe, Co, Rb, Sr, Y, Zr, Rh, Sb, La, Sm, Gd, Yb, Lu, Hf; and Q includes one or more elements selected from F, Cl, Br, I.

4. The lithium manganese nickel composite oxide according to claim 2 or 3, wherein 1≤a / x≤20.

5. The lithium manganese nickel composite oxide according to any one of claims 2-4, wherein, 0.03≤a≤0.15。 6. The lithium manganese nickel composite oxide according to any one of claims 2-5, wherein, 0.002≤x≤0.1。 7. The lithium manganese nickel composite oxide according to any one of claims 2-6, wherein, 0<x + y + z≤0.

3.

8. The lithium manganese nickel composite oxide according to any one of claims 2-7, wherein, 2.4 ≤ I 111 / I 400 ≤ 2.8; 2 ≤ a / x ≤ 10; 0.05 ≤ a ≤ 0.12; 0.01 ≤ x ≤ 0.06; 0.005 ≤ y ≤ 0.05; 0.01 ≤ z ≤ 0.1; 0.01 ≤ x + y + z ≤ 0.1; 0.01 ≤ q ≤ 0.1; 0 ≤ k ≤ 0.1。 9. The lithium manganese nickel composite oxide according to any one of claims 1 - 8, wherein, In the X-ray diffraction pattern of the lithium manganese nickel composite oxide, there is at least one peak between diffraction angles 2θ = 21.5° - 24°, and the ratio of the intensity of the strongest peak between diffraction angles 2θ = 21.5° - 24° to the intensity of the (111) peak is 0 < I (21.5°-24°) / I 111 ≤ 3%.

10. The lithium manganese nickel composite oxide according to any one of claims 1 - 9, wherein, In a battery using the lithium manganese nickel composite oxide as the positive electrode material and Li as the negative electrode material, when charged under the charging condition of 0.1C charging rate, the ratio of the charging capacity in the 3.5 - 4.4V range to the total charging capacity in the 3.5 - 4.95V range of the battery is less than or equal to 15%.

11. The lithium manganese nickel composite oxide according to any one of claims 1-10, wherein, The lithium manganese nickel composite oxide includes one or more of single crystal particles, pseudo - single crystal particles, and secondary particles.

12. The lithium manganese nickel composite oxide according to claim 11, wherein, The number of crystal grains contained in a single secondary particle is 1≤n≤8.

13. The lithium manganese nickel composite oxide according to claim 11 or 12, wherein, The crystal grain shape includes any one or more of quasi - spherical, octahedral, regular shape of octahedron with sharpened and chamfered edges, octahedron with rounded edges, and / or regular polyhedron shape of octahedron with rounded edges and sharpened and chamfered edges.

14. The lithium manganese nickel composite oxide according to any one of claims 1-13, wherein, The volume median particle size of the lithium manganese nickel composite oxide is 2 μm ≤ D V50 ≤ 20 μm.

15. The lithium manganese nickel composite oxide according to any one of claims 1-14, wherein, The pH value of the powder of the lithium manganese nickel composite oxide is 10≤pH≤12.

16. The lithium manganese nickel composite oxide according to any one of claims 1-15, wherein, The specific surface area of the lithium manganese nickel composite oxide is 0 < BET ≤ 0.8 m 2 / g.

17. A positive electrode plate, wherein, It includes a positive electrode material and a positive electrode current collector, and the positive electrode material includes the lithium manganese nickel composite oxide according to any one of claims 1 - 16.

18. A battery, wherein, It includes: A positive electrode plate, a separator, and a negative electrode plate. The separator is located between the positive electrode plate and the negative electrode plate to play a role of isolation. The positive electrode plate includes the positive electrode plate according to claim 17.

19. The battery according to claim 18, wherein, The battery further includes an electrolyte, and the electrolyte solvent of the electrolyte includes one or more of fluorinated carbonates, fluorinated carboxylates, sulfones, and fluorinated ethers.

20. An electrical device, wherein, It includes the battery according to claim 18 or 19.

21. A preparation method of a lithium manganese nickel composite oxide, wherein, It includes: Providing raw materials for the lithium manganese nickel composite oxide; Heat - treating the raw materials of the lithium manganese nickel composite oxide in an oxygen - containing atmosphere to obtain the lithium manganese nickel composite oxide according to any one of claims 1 - 16.

22. The preparation method of the lithium manganese nickel composite oxide according to claim 21, wherein, The heat - treating the raw materials of the lithium manganese nickel composite oxide in an oxygen - containing atmosphere includes: Heating the raw materials of the lithium manganese nickel composite oxide to T1, holding for 2 - 50h to obtain an intermediate of the lithium manganese nickel composite oxide; wherein, 850℃≤T1≤1100℃.

23. The preparation method of the lithium manganese nickel composite oxide according to claim 22, wherein, It further includes: Heating the intermediate of the lithium manganese nickel composite oxide to T2, holding for 0.5 - 20h to obtain a pre - form of the lithium manganese nickel composite oxide; wherein T1 - 200℃≤T2≤T1 and T2≥800℃.

24. The preparation method of the lithium manganese nickel composite oxide according to claim 23, wherein, It further includes: Heating the pre - form of the lithium manganese nickel composite oxide to T3, holding for 5 - 30h to obtain the lithium manganese nickel composite oxide; wherein, 500℃≤T3≤800℃.

25. The preparation method of the lithium manganese nickel composite oxide according to any one of claims 21-24, wherein, The providing raw materials for the lithium manganese nickel composite oxide includes: According to the target component Li 1+a M x Ni 0.5+z Mn 1.5-x-z O 4-k Provide stoichiometric Li2CO3, Ni 0.5+z Mn 1.5-x-z (OH) 4-2x 、M b O c powders, mix them evenly to obtain the raw materials of the lithium manganese nickel composite oxide; Wherein, 0<a≤0.3, 0<x≤0.2, - 0.3≤z≤0.3, 0≤k≤0.2, and M includes one or more elements of sodium (Na), silicon (Si), phosphorus (P), sulfur (S), niobium (Nb), molybdenum (Mo), ruthenium (Ru), tellurium (Te), cerium (Ce), tantalum (Ta), tungsten (W).

Citation Information

Patent Citations

  • Positive electrode active substance and battery

    CN110214389A

  • Electrochemical device and electronic device

    CN113812021A

  • Electrochemical device and electronic device

    CN115053379A

  • Spinel type lithium manganese oxide and method for manufacturing the same

    JP2008156163A

Cited By

  • Lithium ion secondary battery, positive electrode active material, preparation method and electric equipment

    CN121215860A

  • Lithium-ion secondary battery, positive electrode active material, production method, and electric device

    CN121215860B